Comparison of a Novel Herbal Medicine and Omeprazole in the Treatment of Functional Dyspepsia: A Randomized Double-Blinded Clinical Trial - Bordbar, Ghasem (Gastroenterol Res Pract, 2020)
BACKGROUND: The Trachyspermum ammi L. (TA), Anethum graveolens L. (AG), and Zataria multiflora Boiss (ZM) herbal oils are among the most used herbal products in traditional medicine as the antiseptic, anesthetic, carminative, and antispasmodic. However, there are no clinical studies to evaluate the efficacy of the herbs mentioned in the treatment of functional dyspepsia (FD). This study was designed to appraise the efficacy and safety of a novel herbal medicine consisting of ZM, AG, and TA essential oils compared to omeprazole in FD treatment. METHODS: The present study was a randomized double-blind clinical trial with parallel groups in Iran. Patients in control and intervention arms received omeprazole 20 mg once a day and 250 mg soft-gel capsules containing 180 mg of essential oils of ZM, AG, and TA twice a day for two weeks, respectively. The primary outcome was the sufficient response rate in the postprandial distress syndrome (PDS) and/or epigastric pain syndrome (EPS) at the end of the intervention. Secondary outcomes were the improvement rate in the PDS, EPS, Gastrointestinal Symptom Rating Scale (GSRS), and quality of life scores. Also, safety and tolerability were assessed. RESULTS: The within-group comparison of EPS, PDS, total GSRS, GSRS Pain, and GSRS Dyspepsia scores with that at the end of the treatment indicated a significant reduction in both control and intervention groups (p < 0.001). However, after two weeks of treatment, the herbal medication and omeprazole arms were significantly different in the sufficient response rate based on PDS (p < 0.01) and EPS (p < 0.05) scores (78.3% (18/23) and 73.7% (14/19) in the intervention group vs. 36.4% (8/22) and 40.9% (9/22) in the control group). Also, the mean reduction in EPS (p < 0.05), PDS (p < 0.01), and GSRS (p < 0.001) scores after treatment was significantly higher in the intervention group than control group. CONCLUSION: Based on the study findings, this herbal medicine can be considered as an appropriate treatment of FD. However, a larger multicenter trial is needed to confirm the results of the trial.